Ensuring the halal integrity of the food supply chain through halal suppliers: a bibliometric review. Issue 7 (27th September 2021) - Handayani, Dwi Iryaning; Masudin, Ilyas; Haris, Abdul; Restuputri, Dian Palupi
Abstract : Purpose: This paper aims to provide a brief bibliometric review of previous literature reviews in understanding halal suppliers in the food supply chain to achieve halal standards from upstream to downstream. Design/methodology/approach: The method used was a structured literature review sample of during 2008–2020 totalling 142 articles. The authors use the R-package bibliometric and VOSviewer to find out information about journals, articles, authors, citations, keywords and word hierarchy maps. Findings: The analysis reveals five research clusters: halal supply chain, food supply chain, supply chain integration, halal lifestyle, halal logistics. Research limitations/implications: This study focuses on articles that discuss halal suppliers in the food supply chain. Originality/value: Bibliometric reviews related to suppliers in the halal food supply chain in this study will help explore halal suppliers and be useful for researchers and practitioners in their fields as well as assist supplier management in the halal food supply chain.